Pacemaker Lead Endocarditis Investigated with Intracardiac Echocardiography: Factors Modulating the Size of Vegetations and Larger Vegetation Embolic Risk during Lead Extraction - Carlo Caiati; Paolo Pollice; Mario Erminio Lepera; Stefano Favale (MDPI AG, 2019)
Lead pacemaker infection is a complication on the rise. An infected oscillating mass attached to the leads (ILV) is a common finding in this setting. Percutaneous extraction of the leads and of the device is the best curative option. However, extraction of leads with large masses can be complicated by pulmonary embolism. The aim of this study was to understand the factors associated with large ILV using a sophisticated ultrasound technique to visualize the masses, namely intracardiac echocardiography (ICE), and investigate whether larger masses induce more complications during and after extraction. Percutaneous lead extraction and peri-procedural ICE were done in 36 patients (pts) (75 ± 11 years old, 74% males). Vegetations (max dimension = 8.2 ± 4.1 mm) in the right cavity were found in 26 of them, mostly adhering to the leads. We subdivided the patients into 2 groups: with vegetation size < 1 cm (18 pts) and vegetation size ≥ 1 cm (8 pts). By univariate analysis, we found that patients in group 1 were more often taking anticoagulation therapy (p = 0.03, Phi (Phi coefficient) = −0.5, OR [odds ratio] 0.071) and had signs of local pocket infection (p = 0.02, Phi = −0.52, OR 0.059) while significantly more patients in group 2 had diabetes (p = 0.08, Phi = 0.566, OR 15); moreover the patients in group 2 showed a trend toward a more frequent positive blood culture (p = 0.08, Phi = 0.39, OR 5.8) and infection with coagulase negative staphylococci (p = 0.06, Phi = 0.46, OR 8.3). At multivariate analysis, only 3 factors (diabetes, younger age and anticoagulation therapy) were independently associated with ILV size: diabetes, associated with larger vegetations (group 2), showed the largest beta value (0.44, p = 0.008); age was inversely correlated with ILV size (beta value = −32, p = 0.038), and anticoagulation therapy (beta value = −029, p = 0.048) was more commonly associated with smaller vegetations (group 1). Larger ILV were not associated with more complications or death during or after the extraction. Conclusion: diabetes, anticoagulation therapy and age are independent predictors of lead vegetation size. The embolic potential of large ILV during extraction was modest, so ILVs >1cm are not a contraindication to percutaneous extraction of infected leads.